REGENERASI RUMPUT LAUT Gracilaria sp. MELALUI PROPAGASI SECARA EX VITRO - Siti Fadilah; Dhini Arum Pratiwi (Jurnal Kelautan, 2019)
ABSTRACT This study aims to observe the growth of Gracilaria sp. seaweed seedlings through ex vitro propagation. Thallus was cut into thallus fragments measuring ± 2-3 cm. The treatments tested were different types of nutrients and thallus densities. The nutrients used were Provasoli Enriched Sea Water (PES) 20 mL/L, organic fertilizer A (0,05 mL/L), organic fertilizer B (0,05 mL/L) and without fertilizer; while the densities of the thallus fragment tested were 2 g/L; 2,5 g/L and 3 g/L. Thallus fragments were maintained for 8 weeks with media renewal and thallus weighing every week. Shoot length was measured and number of shoots was calculated at the end of the observation. Then, the seedlings were acclimatized at the sea for 8 weeks by binding every 10 thallus fragments to each clump rope in a net box with a side length of 50 cm. Growth was observed by weighing thallus fragments every 4 weeks. The results showed that organic fertilizer A provided better seedling growth compared to other types of fertilizers. The highest Daily Growth Rate (DGR) and shoot length occurred at a density of 2 g/L, but the number of shoots at three densities did not differ at an average of 5 shoots per thallus fragment. The highest average DGR of seedlings during acclimatization reached 4,85%/day in the first month, then decreased to 2,05%/day in the second month. Ex vitro propagation can be used as an alternative effort to propagate the seedlings of Gracilaria sp. by paying attention to the physical condition of the growth environment, especially the temperature and light intensity. Keywords: ex vitro, Gracilaria sp., propagation, regeneration ABSTRAK Penelitian ini bertujuan untuk mengamati pertumbuhan bibit rumput laut Gracilaria sp. melalui propagasi ex vitro. Talus dipotong menjadi fragmen talus berukuran ±2-3 cm. Perlakuan yang diuji yaitu jenis nutrisi dan kepadatan talus yang berbeda. Nutrisi yang digunakan adalah Provasoli’s Enriched Seawater (PES) sebanyak 20 mL/L, pupuk organik A (0,05 mL/L), pupuk organik B (0,05 mL/L) dan tanpa pupuk; sedangkan kepadatan fragmen talus yang yang diuji adalah 2 g/L; 2,5 g/L dan 3 g/L. Fragmen talus dipelihara selama 8 minggu dengan pembaruan media dan penimbangan bobot talus setiap minggu. Panjang tunas diukur dan jumlah tunas dihitung di akhir pengamatan. Kemudian, bibit diaklimatisasi di laut selama 8 minggu dengan mengikat tiap 10 fragmen talus pada tiap tali rumpun dalam kotak hapa dengan panjang sisi 50 cm. Pertumbuhan diamati dengan menimbang fragmen talus setiap 4 minggu. Hasil penelitian menunjukkan bahwa pupuk organik A memberikan pertumbuhan bibit yang lebih baik dibandingkan jenis pupuk yang lain. Laju Pertumbuhan Harian (LPH) dan panjang tunas tertinggi terjadi pada kepadatan 2 g/L, namun jumlah tunas pada tiga kepadatan tidak berbeda yaitu rata-rata 5 tunas per fragmen talus. Rataan LPH tertinggi saat aklimatisasi mencapai 4,85 %/hari pada bulan pertama, kemudian menurun menjadi 2,05 %/hari di bulan kedua. Propagasi ex vitro dapat dijadikan salah satu upaya alternatif perbanyakan bibit Gracilaria sp. dengan memperhatikan kondisi fisik pemeliharaan, terutama suhu dan intensitas cahaya. Kata kunci : ex vitro, Gracilaria sp., propagasi, regenerasi